A survey for variable young stars with small telescopes: VI – Analysis of the outbursting Be stars NSW 284, gaia 19eyy, and VES 263. Issue 4 (14th February 2023) - Froebrich, Dirk; Hillenbrand, Lynne A; Herbert, Carys; De, Kishalay; Eislöffel, Jochen; Campbell-White, Justyn; Kahar, Ruhee; Hambsch, Franz-Josef; Urtly, Thomas; Popowicz, Adam; Bernacki, Krzysztof; Malcher, Andrzej; et al.
ABSTRACT: This paper is one in a series reporting results from small telescope observations of variable young stars. Here, we study the repeating outbursts of three likely Be stars based on long-term optical, near-infrared, and mid-infrared photometry for all three objects, along with follow-up spectra for two of the three. The sources are characterized as rare, truly regularly outbursting Be stars. We interpret the photometric data within a framework for modelling light-curve morphology, and find that the models correctly predict the burst shapes, including their larger amplitudes and later peaks towards longer wavelengths. We are thus able to infer the start and end times of mass loading into the circumstellar discs of these stars. The disc sizes are typically 3 – 6 times the areas of the central star. The disc temperatures are ∼40 per cent, and the disc luminosities are ∼10 per cent of those of the central Be star, respectively. The available spectroscopy is consistent with inside-out evolution of the disc. Higher excitation lines have larger velocity widths in their double-horned shaped emission profiles. Our observations and analysis support the decretion disc model for outbursting Be stars.